IL-6 modulation for COVID-19: the right patients at the right time?. Issue 4 (9th April 2021) - Ascierto, Paolo Antonio; Fu, Binqing; Wei, Haiming
Abstract : The ongoing pandemic caused by the novel coronavirus SARS-CoV-2 has disrupted the global economy and strained healthcare systems to their limits. After the virus first emerged in late 2019, the first intervention that demonstrated significant reductions in mortality for severe COVID-19 in large-scale trials was corticosteroids. Additional options that may reduce the burden on the healthcare system by reducing the number of patients requiring intensive care unit support are desperately needed, yet no therapy has conclusively established benefit in randomized studies for the management of moderate or mild cases of disease. Severe COVID-19 disease is characterized by a respiratory distress syndrome accompanied by elevated levels of several systemic cytokines, in a profile that shares several features with known inflammatory pathologies such as hemophagocytic lymphohistiocytosis and cytokine release syndrome secondary to chimeric antigen receptor (CAR) T cell therapy. Based on these observations, modulation of inflammatory cytokines, particularly interleukin (IL)-6, was proposed as a strategy to mitigate severe disease. Despite encouraging recoveries with anti-IL-6 agents, especially tocilizumab from single-arm studies, early randomized trials returned mixed results in terms of clinical benefit with these interventions. Later, larger trials such as RECOVERY and REMAP-CAP, however, are establishing anti-IL-6 in combination with steroids as a potential option for hypoxic patients with evidence of hyperinflammation. We propose that a positive feedback loop primarily mediated by macrophages and monocytes initiates the inflammatory cascade in severe COVID-19, and thus optimal benefit with anti-IL-6 therapies may require intervention during a finite window of opportunity at the outset of hyperinflammation but before fulminant disease causes irreversible tissue damage—as defined clinically by C reactive protein levels higher than 75 mg/L.